A Comparison of Training Methods on the Acquisition of Automotive Product Knowledge. Issue 3 (September 2016) - Fante, Rhiannon M.; Bucklin, Barbara R.; Diener‐Ludwig, Lori; Sundberg, Daniel B.; Dickinson, Alyce M.
Abstract : The purpose of this study was to compare the effects of a traditional training program with a fluency‐building training program on the acquisition of automotive product knowledge in a lab setting. The effects were assessed by how accurately and quickly participants responded on a product‐knowledge test. Results indicated that participants who completed the fluency training responded faster and more accurately than control groups immediately after the study. However, the difference between the fluency group and the group that received study objectives disappeared when retention was assessed several weeks after training. The difference remained between these groups and a group that did not receive study objectives. The results were used to modify globally delivered training. This study extended previous studies by examining the effects of training designed to teach product knowledge to sales representatives in automotive dealerships and illustrates the benefits of collaboration between academic researchers and professional trainers.